2023
DOI: 10.1039/d3nj04425d
|View full text |Cite
|
Sign up to set email alerts
|

Lewis acidic deep eutectic solvents as catalysts for rosin polymerization

Yali Yu,
Fengli Yu,
Lu Li
et al.

Abstract: A green and effective catalytic system for rosin polymerization using a recyclable Lewis acidic DES catalyst has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…This result fully showed that too weak acid strength could not achieve a rational catalytic effect, and too strong acid strength will cause some side reactions. This result was in good agreement with the previous literature, 22 so rosin polymerization needed appropriate acid strength.…”
Section: Study On Rosin Polymerization 331 Catalytic Performances Of ...supporting
confidence: 93%
See 1 more Smart Citation
“…This result fully showed that too weak acid strength could not achieve a rational catalytic effect, and too strong acid strength will cause some side reactions. This result was in good agreement with the previous literature, 22 so rosin polymerization needed appropriate acid strength.…”
Section: Study On Rosin Polymerization 331 Catalytic Performances Of ...supporting
confidence: 93%
“…The green synthesis technology of polymerized rosin under a deep eutectic solvent system is shown in Figure 2. Using 15 g of rosin as raw material 22 and 17.20 mL of toluene as a solvent, it was carried out in a 150 mL threenecked flask. First of all, the rosin needed to be completely dissolved in the solvent by mechanical stirring at 70 °C, and then DES was added into the reaction liquid, the amount of which was 30% (m DES :m rosin ).…”
Section: Preparation Of Polymerized Rosinmentioning
confidence: 99%
“…Diminishing the sizing rate in the desizing process can mitigate the emission of organic pollutants with high biochemical oxygen demand (BOD), including fibers, desizing agents, and sizing materials. Furthermore, this can ameliorate the quality of weaving, reduce operational costs, minimize wastage of sizing materials, and conserve thermal energy [4][5][6]. Consequently, the development of accurate and rapid sizing rate detection technology holds substantial practical significance.…”
Section: Introductionmentioning
confidence: 99%